Epigenética e HVI-1: a participação das histonas na infecção e no tratamento - Lima, Mariana Leão de; Janini, Luiz Mario Ramos; Santos, Lucilene Delazari dos [UNESP] (My University, 2010)
Previously used as retroviruses vector silencing, epigenetic assays have become a key for understanding high complexity phenomena that is not explained yet. The effect of DNA polymer interaction on intramolecular and intermolecular level has implications on successful or unsuccessful infection, transcription activation and inactivation. This review aims to discuss something about epigenetic concepts and its application on treatment of HIV-harboring patients. Among the perspectives, the most important one is the development of new pharmacological agents to address the purge of latent HIV-1 reservoirs.

Inicialmente utilizados para silenciar vetores retrovirais, os mecanismos epigenéticos têm se tornado chave para a explicação de fenômenos complexos até então não compreendidos. O efeito da interação do polímero de DNA intramolecular e intermolecularmente afeta, inclusive, o sucesso e o insucesso da infecção viral, a ativação e a inativação da transcrição. Esta revisão tenta discutir um pouco dos conceitos e aplicações da epigenética no tratamento de pacientes portadores do HIV-1. Dentre as perspectivas, a principal é o desenvolvimento de novas drogas que sejam capazes de purgar os reservatórios de latência do HIV-1.
HIV and epigenetics: Histone role in HIV-1 infection and treatment
Keywords: HIV-1; Treatment; Epigenetics; Histones; DNA; HIV-1; Tratamento; Epigenética; Histonas; DNA